Hegel, Peirce, and Aristotle on the "Geometric" Logic of Practical Reason - Redding, Paul (Revista Eletrônica Estudos Hegelianos, 2022)
This article examines a convergence between approaches to practical reason in the logics of Aristotle, Hegel and Peirce around a form of non-demonstrative inference that proceeds in a regressive way from conclusions to premises of a deductive inference. In Nicomachean Ethics Aristotle had described a type of practical deliberation in this way and had likened it to a type of inference used by geometers in relation to their constructed diagrams. Peirce would describe a similar form of inference he called “abduction”, and parallels between Peirce’s three inference forms—deduction, induction, and abduction—are found in Hegel’s treatment of the three figures of Aristotle’s syllogism in Book III of The Science of Logic. It is argued that this postulation of a third inference form in Aristotle coheres with Hegel’s Platonic reconstruction of Aristotle’s formal syllogistic and his related separation of the categories of singularity and particularity.
Keywords: Hegel; Peirce; Aristotle; Abduction; Practical Logic; Geometric Logic